Internet of Things, Blockchain, and Artificial Intelligence for Green Governance – A Proposed Model - Surjandy, Surjandy; Fernando, Erick (Universitas Negeri Padang, 2025)
Global climate change remains a significant challenge that occurs in numerous regions worldwide. Countries are persistently undertaking various steps, including the development of green governance model to address this issue. Nonetheless, the implementation of these eco-friendly goods encounters numerous challenges, one of which is to the precision of data regarding green products. Conversely, substantial study has been conducted on three burgeoning technologies—blockchain, the Internet of Things (IoT), and artificial intelligence (AI)—which are progressively employed to enhance the green governance model. This qualitative study aims to conduct an in-depth exploration using 809 documents from the Scopus database, with articles from the past 10 years, and employs Biblioshiny techniques for data analysis to form a model that leverages these three technologies as a framework for governing and implementing green insurance products. These three technologies provide distinct qualities that can synergistically enhance the development of green data products. This research significantly aids the implementation of the green governance model across various industries and sectors, while also supporting governmental monitoring